Ripley's believe it or not! dare to look! - Tibballs, Geoff (Ripley's believe it or not!, 2013)
The tenth collection of amazing stories and incredible facts from around the world features hidden content through a companion app and includes stories about a family of hirsute "werewolf sisters" and a man who hangs weights from his eye sockets.